N‐acetylaspartate availability is essential for juvenile survival on fat‐free diet and determines metabolic health. Issue 12 (1st November 2019) - Hofer, Dina C.; Zirkovits, Gabriel; Pelzmann, Helmut J.; Huber, Katharina; Pessentheiner, Ariane R.; Xia, Wenmin; Uno, Kyosuke; Miyazaki, Toh; Kon, Kanta; Tsuneki, Hiroshi; Pendl, Tobias; Zoughbi, Wael Al; et al.
Abstract : N‐acetylaspartate (NAA) is synthesized by aspartate N ‐acetyltransferase (gene: Nat8l ) from acetyl‐coenzyme A and aspartate. In the brain, NAA is considered an important energy metabolite for lipid synthesis. However, the role of NAA in peripheral tissues remained elusive. Therefore, we characterized the metabolic phenotype of knockout (ko) and adipose tissue‐specific (ako) Nat8l ‐ko mice as well as NAA‐supplemented mice on various diets. We identified an important role of NAA availability in the brain during adolescence, as 75% of Nat8l ‐ko mice died on fat‐free diet (FFD) after weaning but could be rescued by NAA supplementation. In adult life, NAA deficiency promotes a beneficial metabolic phenotype, as Nat8l ‐ko and Nat8l ‐ako mice showed reduced body weight, increased energy expenditure, and improved glucose tolerance on chow, high‐fat, and FFDs. Furthermore, Nat8l ‐deficient adipocytes exhibited increased mitochondrial respiration, ATP synthesis, and an induction of browning. Conversely, NAA‐treated wild‐type mice showed reduced adipocyte respiration and lipolysis and increased de novo lipogenesis, culminating in reduced energy expenditure, glucose tolerance, and insulin sensitivity. Mechanistically, our data point to a possible role of NAA as modulator of pancreatic insulin secretion and suggest NAA as a critical energy metabolite for adipocyte and whole‐body energy homeostasis.—Hofer, D. C., Zirkovits, G., Pelzmann, H. J., Huber, K., Pessentheiner, A. R., Xia, W., Uno, K., Miyazaki, T., Kon, K., Tsuneki, H., Pendl, T., Al Zoughbi, W., Madreiter‐Sokolowski, C. T., Trausinger, G., Abdellatif, M., Schoiswohl, G., Schreiber, R., Eisenberg, T., Magnes, C., Sedej, S., Eckhardt, M., Sasahara, M., Sasaoka, T., Nitta, A., Hoefler, G., Graier, W. F., Kratky, D., Auwerx, J., Bogner‐Strauss, J. G. N‐acetylaspartate availability is essential for juvenile survival on fat‐free diet and determines metabolic health. FASEB J. 33, 13808‐13824 (2019). www.fasebj.org